2021
DOI: 10.1021/acs.biomac.0c01600
|View full text |Cite
|
Sign up to set email alerts
|

Bottom-up Construction of Xylan Nanocrystals in Dimethyl Sulfoxide

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 64 publications
0
24
0
Order By: Relevance
“…Purification of xylan leading to crystals suggests the possibility of using biotechnology to remove specific side groups common to xylan that would aid in controlling the formation of xylan single crystals in aqueous suspensions. In addition, xylan has been shown to co-crystalize with DMSO in a twofold axis that creates needles, such as crystals [ 140 ]. If optimized, these highly anisotropic crystals would provide an interesting platform for hemicelluloses to be used in nanotechnology applications, such as photonic films.…”
Section: Lignocellulosic Biomass Chemical Constituentsmentioning
confidence: 99%
“…Purification of xylan leading to crystals suggests the possibility of using biotechnology to remove specific side groups common to xylan that would aid in controlling the formation of xylan single crystals in aqueous suspensions. In addition, xylan has been shown to co-crystalize with DMSO in a twofold axis that creates needles, such as crystals [ 140 ]. If optimized, these highly anisotropic crystals would provide an interesting platform for hemicelluloses to be used in nanotechnology applications, such as photonic films.…”
Section: Lignocellulosic Biomass Chemical Constituentsmentioning
confidence: 99%
“…The backbones of xylans in hardwood and graminaceous plants are partially acetylated, but softwood xylans are not acetylated. Original xylans in plants are in an amorphous state [4], but deacetylated and low-branched xylans can form a crystalline structure with solvent molecules, such as water and dimethyl sulfoxide (DMSO) [5][6][7]. Due to the insufficient studies on xylan crystallization, the applications of xylans have been mainly focused on bulk applications, such as films and coatings [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…The applications of xylan could be greatly broadened if xylan crystals are nano-sized, as nanocrystals of some biopolymers, e.g., cellulose, chitin/chitosan, and starch, have been widely used in advanced functional materials, such as biological scaffolds, drug carriers, optical materials, permselective membranes, polymer electrolytes, and emulsion stabilizers [11,12]. However, preparing xylan nano-crystals with controllable size and shape is difficult and has only been reported on in a few studies [7,13]. Chanzy et al reported the desizes of xylan crystals by enzymatic degradation, but the enzyme degrades the xylan crystals from the edge and destroys the crystalized structure [13].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations